Tapering and discontinuation of thrombopoietin receptor agonists in immune thrombocytopenia: Real-world recommendations. (May 2020) - Zaja, F.; Carpenedo, M.; Baratè, C.; Borchiellini, A.; Chiurazzi, F.; Finazzi, G.; Lucchesi, A.; Palandri, F.; Ricco, A.; Santoro, C.; Scalzulli, P.R.
Abstract: Thrombopoietin receptor agonists (TPO-RAs) are currently indicated for continuous treatment of chronic primary immune thrombocytopenia (ITP). However, there is growing evidence that TPO-RAs can also trigger sustained response in 10–30% of cases after treatment tapering and discontinuation. Therefore, at least for selected responding patients, it might be rational to plan TPO-RA interruption to exploit off-treatment response. Intriguingly, complete or partial responses with TPO-RAs are frequently observed when treatments are initiated early, suggesting that unknown immune-related mechanisms may be involved in this phenomenon. The sustained responses observed after interruption of TPO-RAs may be interpreted as a recovery of immunological tolerance; thus, the re-establishment of immunological equilibrium might be primarily responsible for the observed off-treatment effect. Importantly, these findings may indicate that anticipated TPO-RA usage can lead to improved responses, and that optimized tapering and interruption in selected patients can furthermore improve prognoses. On the base of this rationale, a series of real-life considerations have been generated by a panel of Experts to elucidate possible novel criteria and modalities to identify subgroups of patients who can benefit from tapering and/or discontinuation of TPO-RAs. Towards this aim, the results of a survey of ITP experts are herein reported, reflecting a snapshot of current real-life experience on early discontinuation of TPO-RA-based therapy. The present manuscript also highlights the importance of future translational studies on novel prognostic and predictive biomarkers that can stratify patients and facilitate the clinical choice for second-line treatment of ITP.